Himiko and Japan's elusive chiefdom of Yamatai : archaeology, history, and mythology - Kidder, J. Edward (Jonathan Edward) (University of Hawai'i Press, 2007)
The third-century Chinese chronicle Wei zhi (Record of Wei) is responsible for Japan's most enduring ancient mystery. This early history tells of a group of islands off the China coast that were dominated by a female shaman named Himiko. Himiko ruled for more than half a century as head of the largest chiefdom, traditionally known as Yamatai, until her death in 248. Yet no such person appears in the old Japanese literature. Who was Himiko and where was the Yamatai she governed? In this, the most comprehensive treatment in English to date, a senior scholar of early Japan turns to three sources--historical, archaeological, and mythological--to provide a multifaceted study of Himiko and ancient Japanese society.